ACTS - The African Centre for Technology Studies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The African Centre for Technology Studies (ACTS) is a non-profit institution that conducts policy research, undertakes training and raises public awareness on the application of science and technology to sustainable development. ACTS started...